Elevated fingernail cortisol levels in major depressive episodes. (February 2018) - Herane-Vives, Andres; Fischer, Susanne; de Angel, Valeria; Wise, Toby; Cheung, Eric; Chua, Kia-Chong; Arnone, Danilo; Young, Allan H.; Cleare, Anthony J.
Highlights: Depressed patients have increased cortisol levels in comparison to controls using specimens that measure aggregate cortisol levels over a period of fifteen days. Increased cortisol levels may be only explained for those severe episodes with non-reactive mood and more prominent melancholic symptoms. Depressed patients with severe fatigue were characterised by decreased cortisol levels. Abstract: Background: The extent to which cortisol levels are elevated in major depressive episodes (MDE), and hence could act as a biomarker of illness, remains unclear. Although patient characteristics may explain some of this variation – for example elevated cortisol being more often found in patients with severe, psychotic or melancholic depression – problems with the methods used to measure cortisol may also have contributed to the inconsistent findings. Fingernails are a novel sample that can be used to assess aggregate cortisol concentrations over a 15-day period, and may provide a more accurate reflection of longer term cortisol level changes in MDE and help clarify this issue. This methodology has not yet been utilised in MDE. Methods: Cortisol levels reflecting a period of 15 days were measured using fingernails in a group of 26 subjects experiencing a major depressive episode (MDE) and in an age and gender matched group of 45 healthy controls. Results: Depressed subjects showed significantly higher mean cortisol levels measured in fingernails when compared with control subjects. Higher levels of cortisol were associated with higher depression severity scores, a diagnosis of non-reactive depression, and more prominent melancholic symptoms. Conversely, fatigue was negatively correlated with cortisol levels. Conclusion: There is elevated cortisol in MDE when assessed using an aggregate measure over two weeks.Alterations in fingernail cortisol correlate with key clinical symptoms and subtypes of depression.